Ozone trends on equatorial and tropical regions of South America using Dobson spectrophotometer, TOMS and OMI satellites instruments. (July 2020) - Sousa, C.T.; Leme, N.M.P.; Martins, M.P.P.; Silva, F.R.; Penha, T.L.B.; Rodrigues, N.L.; Silva, E.L.; Hoelzemann, J.J.
Abstract: The ozone layer filters solar ultraviolet radiation and is affected by several photochemical and dynamical processes in the atmosphere. Stratospheric ozone formation takes place primarily in tropical regions and it is the consequence of reactions between atmospheric oxygen and the ultraviolet solar radiation. For the purpose of this paper, the atmospheric TOC (Total Ozone Content) measurements are calculated using Dobson spectrophotometers, in conjunction of satellite data of TOMS (Total Ozone Mapping Spectrometer), and OMI (Ozone Monitoring Instrument), at Cachoeira Paulista (22.7 o S, 45.0 o W) (CP) and Natal (5.8 o S, 35.2 o W) (NT), Brazil. The time series considered extend from 1974 to 2013 for CP and from 1978 to 2013 for NT. The mean differences in ozone values between Dobson and TOMS, and between Dobson and OMI, are about 3% and 2%, respectively. The correlations of the Dobson spectrophotometers with TOMS are inferior to the correlations of Dobson to OMI data, due to the improved retrieval and algorithm of the more recent OMI instrument. The observed long-term ozone trends obtained for CP and NT with Dobsons, are: −2.76%, for the period of 1974–2013, and -0.78%, for the period of 1978–2013, respectively. The trend in TOC per decade is of −0.71 ± 0.4% at CP, and of −0.22 ± 0.2%, at NT. The estimated seasonal trends for CP in June-July-August are −3.3%, compared to NT, which yields −1% in the same period. NT seasonal trend for December-January-February is −1.3%. This shows that there is a more significant decrease at CP than at NT, which agrees with the fact that the most active ozone production occurs near the equator. The average ozone amounts were 268.3 ± 13.1 DU for CP and 265.9 ± 10.9 DU for NT, and a seasonal cycle with a minimum of 256.0 DU at CP and NT in autumn and maximum of 283 DU at CP and 279 DU at NT in spring, of southern hemisphere. Highlights: Difference estimation values between Dobson at CP/NT, and TOMS/OMI, were 3% and 2%. The long-term ozone trends at two stations are −2.76%, and −0.78%, respectively. Average ozone amounts at each station was 268.8 ± 9.5 DU for CP and 266.8 ± 7.4 DU at NT. Seasonal cycle with a minimum of 256 DU at CP and NT, in autumn. Seasonal cycle with maximum of 283 DU at CP and 279 DU at NT, in spring.